HUBUNGAN PENGAWASAN SUPERVISOR DENGAN DISIPLIN KERJA KARYAWAN HOUSEKEEPING DI HOTEL ROCKY PLAZA PADAN - Arlinda, Putri; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2016)
The purpose of this research is to examine the correlation between the supervisor supervision with working discipline of the housekeeping employee at Rocky Plaza Hotel Padang. The type research is correlational. Population in this research are amounted to 30 people. The sampling technique is non probability sampling, by using saturated sampling. Sample in this research are amounted to 30 people. Data collection using a questionnaire based on a Likert scale that has been tested for validity and reliability. The results of the research indicates that the supervisor supervison at Rocky Plaza Hotel Padang is good (73,4%), and for working discipline of the housekeeping employee at Rocky Plaza Hotel Padang is good (80%). The results also indicate that the presence of a medium significant correlation between supervisor supervision and working discipline of the housekeeping employee at Rocky Plaza Hotel Padang with correlation coefficient values (0,515) and significant values (0,004). Keywords: Supervision Supervisor, Discipline, Housekeeping EmployeeÂ